Sequentially Reinforced Additive Coating for Transparent and Durable Superhydrophobic Glass - Zhao, Shuangjie (Langmuir : the ACS journal of surfaces and colloids, 2018)
Now that there are various routes to prepare superhydrophobic surfaces for self-cleaning, anti-icing, liquid collecting, etc., attentions are moving toward low-cost upscaling of routes and increasing the reliability for actual applications. However, the required micro-nano structures for superhydrophobicity are light scattering and very vulnerable to abrasion. This intrinsically conflicts with the transparency and durability of superhydrophobic glass, which are the major barriers for its commercialization. In this study, we present a novel sequentially reinforced additive coating (SRAC) process to realize robust and transparent micro-nano structured film with tough intergranular sintering. A benign aqueous-based ink with poly(furfuryl alcohol) (PFA) and silica species is carefully designed and sprayed on glass to enable self-phase separation and morphology construction. The coatings reach the static contact angle (SCA) for water over 166° and withstand a 6H pencil scratching, the cross-cut test, and sand abrasion. Moreover, we also performed a 90 day outdoor performance test and the glass maintained superhydrophobicity with an SCA of 154°. These results provide a low-cost waterborne ink formula, and the high throughput and upscalable SRAC process could be a convenient technology for the fabrication of large area, robust superhydrophobic coatings